A comparative study on the tribological behavior of mono&proportional hybrid nanofluids for sustainable turning of AISI 420 hardened steel with cermet tools. (January 2022) - Yıldırım, Çağrı Vakkas; Şirin, Şenol; Kıvak, Turgay; Sarıkaya, Murat
Abstract: The current study examines the influence of various mono and proportional hybrid nanofluids prepared with multi-walled carbon nanotube (MWCNT), alumina (Al2 O3 ) and molybdenum disulphide (MoS2 ) on the performance of cermet tools in turning of AISI 420 hardened steel. First, mono-nanofluids were prepared using each nanoparticle separately (i.e., Al2 O3, MWCNT and MoS2 ). Afterward, hybrid nanofluids were prepared at three different nanoparticle mixture ratios i.e., particle A:particle B of 1:1 (50 vol% + 50 vol%), particle A:particle B of 1:2 (33.34 vol% + 66.66 vol%), particle A:particle B of 2:1 (66.66 vol% + 33.34 vol%) in a constant volume concentration of 0.6%. Prepared nanofluids (nine different hybrid nanofluids and three different mono nanofluids) were cooperated with the MQL system and their effects on the machinability characteristics such as surface roughness, surface topography, temperature, tool flank wear, and wear mechanisms were investigated. The results were compared with dry and base-fluid MQL assisted cutting results. The surface roughness was decreased by 41.54%, 37.38% and 30.62% through Al2 O3 :MoS2 (2:1), Al2 O3 :MoS2 (1:2) and Al2 O3 :MoS2 (1:1) hybrid nanofluids compared to base fluid, respectively. It was found that different ratios of one more than nanoparticles have a significant effect on the synergistic effect. Based on the all experimental results, it can be concluded that it is necessary to optimize the nanoparticle ratios used in the preparation of hybrid nanofluids.